U-TH-PB DATING OF PHOSPHATE MINERALS - Harrison T.M.; Catlos E.J.; Montel J.-M. (My University, 2002)
The dominant occurrence of phosphate minerals in crystalline rocks is as accessory phases, most notably apatite, monazite, and xenotime. Because these minerals tend, to varying degrees, to partition U and Th into their structures they can often contain the majority of those elements in a rock. These three phases, again to varying degrees, tend not to incorporate significant amounts of Pb during crystallization and thus were early candidates for utilization as U-Th-Pb geochronometers. The ideal U-Th-Pb geochronometer would be a phase that is stable over all possible environmental conditions and is quantitatively retentive of parent and daughter isotopes. In fact, the silicate zircon comes reasonably close to meeting these criteria. Zircon has a broad stability field, is refractory under a wide variety of geologic environments (e.g., weathering, sedimentary transport, anatexis, and metamorphism), and can be highly retentive of daughter products in the U-Th-Pb decay system. However, the limit of zircon as an ideal chronometer lies only in its limited resistance to auto-irradiation damage that can render it metamict. The phosphate minerals apatite, monazite and xenotime have a more restricted range of stability and, to varying degrees, are incompletely retentive of Pb under crustal conditions, but they are resilient to radiation damage. Thus interpretation of results from these geochronometers requires a greater understanding of their structure, stability, and kinetic properties than does zircon. This chapter is aimed at providing the reader with an introduction to those characteristics that will facilitate interpretation of the occasionally problematic nature of phosphate U-Th-Pb dating results.